Pembentukan kerangka kerja amalan terbaik bagi pengurusan harta tanah pihak berkuasa tempatan (PBT) - Mohammed, Miswan @ Abdul Hakim (UTM, 2005)
Many initiatives executed by local authority to ensure their service will improve continuously. Those initiatives were involving various actions implemented by local authority including setup the property management division in each organisations. Local authority property management division (LAPMD) is a divison that usually been given the responsibility to manage local authority properties. Nevertheless, the roles that have been played by these divisions are not uniformed for they have diversified objectives and functions and also different from each other. This situation occurs from a condition where these departments were first established to have their own benefits thus leaving behind the needs for a uniform organisational foundation. Therefore, this non unified condition has led to various negative effects particularly to local authority organisations themselves hence showing that their practice in managing property is still at an unsatisfactory level. On the other hand, this research is carried out to help achieve four main objectives among which are to identify the needs for establishing the LAPMD, to identify the motive in determining the objectives of LAPMD, to identify the main functions of LAPMD and to develop frameworks in deploying each main function. This research has been done in four levels of execution which are literature review, pilot study, survey study and benchmarking study. Data gathered from this research has been analysed through qualitative and quantitative approaches which includes Alpha Cronbach analysis, Mann-Whitney analysis, Kruskal-Wallis analysis, frequency analysis, min analysis, correlation analysis and content analysis. The research findings have identified seven factors that can be considered as the needs for the establishment of LAPMD. Their service motives can be concluded as the most important for LAPMD objectives. On the other hand, tenancy management function and maintenance management function have been identified as two main functions of LAPMD. Furthermore, this research has developed a framework for the tenancy management function with 16 working steps and also a framework for maintenance management function with 18 working steps. All working steps have been categorised under four basic management processes among which are planning, organising, executing and controlling.